The Relationship Between Family Support and The Eating Culture Of Post Partum Mothers In The Work Area Of The Muncan Health Center - Sumiati, Eti; Endy Bebasari Ardhana Putri; Dewi Ratna Wulan; Rosita Khaerina (Florea : Jurnal Biologi dan Pembelajarannya, 2024)
The postpartum period is a process that begins after the placenta separates and ends when the uterus returns to its pre-pregnancy state. At that time, the nutritional needs of postpartum mothers increased from before, because they were needed to prepare for breastfeeding and help speed up the recovery process so that family support to accompany postpartum mothers in consuming nutritious food was needed. This study aims to determine the relationship between family support and postpartum mother's eating culture. This study used a correlational descriptive design with a cross sectional approach. The population of this study were all postpartum mothers 0-42 days who were in the working area of ​​the Muncan Health Center in the period from July to August 2021 as many as 76 people. The sampling technique used was total sampling where all postpartum mothers who became the population sampled were 76 people. The instrument used is a questionnaire and the analysis used is the Chi square test. Most postpartum mothers did not get family support, especially instrumental support and informational support, causing most postpartum mothers to practice a culture of abstinence from eating, namely not consuming healthy food recommended by health workers. The p value = 0.018 < 0.05 (α = 0.05), it means that there is a relationship between family support and postpartum mother's eating culture. Family support in assisting postpartum mothers to consume nutritious food has been proven to have a strong influence on the postpartum mother's recovery process. Health workers must be more active in providing continuous health education to the families of postpartum mothers to improve the culture of eating that is not appropriate.